Self-objectification in university women not heterocentrated - Macêdo, Karoliny Viana; Pinheiro, Gilson de Assis (Seven Editora, 2023)
Self-objectification refers to the internalization of the other’s gaze on one’s own body. From studies by Frederickson and Roberts (1997) it is perceived that, in the macho culture, people are objectified, the body becomes sexually objectified, controlled, "the target of looks and criticism". The greater the objectification, the greater the impact on mental health resulting in the occurrence of numerous conditions, such as eating disorders, anxiety, depression, stress and others. There is little research on self-objectification in college women and even less on self-objectification in non-hetero-transgender, transvestite, and non-binary college women. This paper aims to measure self-objectification in non-normative hetero university women. It was observed (1) there is high objectification in transgender, transvestite and non-binary university women. (2) The highest average of self-objectification was with transvestite university women, (3) There is a need to establish policies aimed at non-heterocentric gender relations DOI:https://doi.org/10.56238/ptoketheeducati-043